Effect of Dietary Phytocee and Zist on Broiler Performance and Carcass Characteristics - Ahmed, Mohamed E.; Mohamed, Nasir H.; Abbas, Talha E. (Pakistan Journal of Nutrition, 2015)
The present study was aimed at evaluation of growth performance and carcass characteristics of broiler chicks fed dietary polyherbal formulation Phytocee and Zist. One hundred and twenty day-old, unsexed broilers (Ross 308) with an initial live body weight of 46.78g ± 0.21 were randomly assigned to 3 dietary treatments, each consisting of 4 replicates with 10 birds each. The three starter and finisher experimental diets consisted of control (0.0% phytocee and 0.0% Zist), 0.03% phytocee and 0.03% Zist. Dietary treatments indicated no significant (p>0.05) effect on all live performance parameters through starter, finisher and overall period. However, overall body weight gain, FCR and PER were improved in Zist diet by 10.84, 11.68 and 9.80%, respectively compared to control. Carcass characteristics and internal organs showed no significant (p>0.05) differences in response to dietary treatments. The result of the current study revealed that Zist improves live performance parameters during different growth phases. Based on this finding, Zist could be added to either starter or finisher broiler diet with positive effects on broiler performance.